An electrostatic network with strong connectivity is a phospho-sensor for regulating affinity of Syk–receptor association - Duy P. Hua; Jacob J. Kinnun; Carol Beth Post (Proceedings of the National Academy of Sciences, 2025)
Spleen tyrosine kinase (Syk) mediates early signaling events in immunity by coupling membrane receptors to immune responses. Syk comprises a tandem SH2 (tSH2) regulatory module—two SH2 domains connected by a structured linker—and a kinase domain. The association of tSH2 with a doubly tyrosine-phosphorylated motif (dpITAM) on membrane immunoreceptors is central to controlling Syk’s signaling activity. tSH2-dpITAM association is regulated by Y131-phosphorylation on linker A, distant from the Syk–immunoreceptor binding sites. A unique thermodynamic signature was reported to control this protein–protein interaction by phosphorylation, yet the molecular mechanism for the phosphorylation effect is unknown. Molecular dynamics (MD) simulation affords the detail needed to fill this knowledge deficiency. Long MD simulations revealed a highly correlated interdomain electrostatic network (distance correlation coefficients > 0.75) that is lost upon Y131-phosphorylation. Some of the strongly correlated interdomain pairs carry the same charge or are separated by distances greater than a salt-bridge pair. The strong interdomain connectivity accounts for the single, narrow free energy basin in the domain-structure conformational landscape for unphosphorylated tSH2. Linker phosphorylation disrupts this network and yields a broader free energy landscape with multiple networks formed by the same group of residues adopting alternative interdomain conformations. A salt dependence of NMR rotational tumbling times substantiates the electrostatic nature of tSH2 domain–domain coupling. Syk tandem SH2 is thus a sensor whose conformational plasticity is sensitive to Y131 phosphorylation. This phospho-sensing response provides the basis for an entropically driven regulatory mechanism that is so-far unique to Syk–immunoreceptor protein–protein association.